1997
DOI: 10.1046/j.1570-7458.1997.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

The responses of the cabbage seed weevil Ceutorhynchus assimilis to volatile compounds from oilseed rape in a linear track olfactometer

Abstract: The cabbage seed weevil, Ceutorhynchus assimilis Payk. [syn. Ceutorhynchus obstrictus (Marsham)] (Coleoptera: Curculionidae), a crucifer‐feeding insect, is a pest of oilseed rape (Brassica napus L.). It is known to be attracted by isothiocyanates, crucifer‐specific volatiles that are metabolites of the glucosinolates. The responses of this insect to other electrophysiologically‐active volatiles from rape were tested in a linear track olfactometer. Attraction was demonstrated to nitriles (phenylacetonitrile, 4‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 18 publications
1
40
0
1
Order By: Relevance
“…In fact, isothiocyanates in particular are known to attract many specialist herbivorous species (reviewed by Wittstock et al 2003) and even to stimulate oviposition (Renwick et al 2006). On the other hand, only a few studies have demonstrated that nitriles attract herbivores, and in general these were less attractive than isothiocyanates (Pivnick et al 1992;Bartlet et al 1997;Smart and Blight 2000;De Vos et al 2008). Whether the preference of P. rapae to oviposit on isothiocyanate-emitting wild-type plants is due to the repellent effect of nitriles or to the stimulating effect of isothiocyanates or both remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, isothiocyanates in particular are known to attract many specialist herbivorous species (reviewed by Wittstock et al 2003) and even to stimulate oviposition (Renwick et al 2006). On the other hand, only a few studies have demonstrated that nitriles attract herbivores, and in general these were less attractive than isothiocyanates (Pivnick et al 1992;Bartlet et al 1997;Smart and Blight 2000;De Vos et al 2008). Whether the preference of P. rapae to oviposit on isothiocyanate-emitting wild-type plants is due to the repellent effect of nitriles or to the stimulating effect of isothiocyanates or both remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The model was reduced by removing non-significant terms and a t-test on the logistic scale (Collet, 1991) was used to test the difference between the percentage of beetles turning towards the floral odour and 50% (the percentage expected when there is no effect on the orientation responses of the beetles). In analyses where the data exhibited overdispersion (where the variance is found to be greater than expected under the binomial assumptions), a heterogeneity factor (see Bartlet et al, 1997) was estimated and used to model this variability in the responses of the pollen beetles. This has the effect of increasing the standard errors associated with the estimated percentage of beetles responding to the floral odours, thus producing wider confidence intervals for these estimates and more conservative tests of treatment effects.…”
Section: Methodsmentioning
confidence: 99%
“…3) is an important pest of oilseed rape in Europe and North America (Lamb, 1989;Bartlet et al, 1997;Girard et al, 1998;Ferguson et al, 1999b), causing reduction in crop yield in heavily infested fields Girard et al, 1998). The cabbage seed weevil is an oligophagous insect that feeds and develops on Brassica species.…”
Section: The Weevils (Ceutorhynchus Spp)mentioning
confidence: 99%
“…In a response study with cabbage seed weevil antenna to volatiles in air entrainment-derived extracts of oilseed rape, using electroantennograms coupled with GC-single cell recording, it was shown that isothiocyanate perception is mediated by three types of olfactory cells, which show differential response to 3-butenyl, 4-pentenyl and 2-phenylethyl isothiocyanate (Blight et al, 1995). The responses of cabbage seed weevil to other electrophysiologically-active volatiles from rape were tested in a linear track olfactometer (Bartlet et al, 1997). Attraction was shown to nitriles (phenylacetonitrile, 4-pentenenitrile and 5-hexenenitrile) and to volatiles emitted by a wider spectrum of plant families, (Z)-3-hexen-1-ol and methyl salicylate.…”
Section: Plants (Brassica Spp)-herbivores (Ceutorhynchus Assimilis)mentioning
confidence: 99%